Comparative morphology of the tongue in free-tailed bats (Chiroptera, Molossidae) - Gregorin, Renato [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2003)
Descriptive and comparative studies on tongue of nineteen Molossidae, one Mystacinidae, and four Vespertilionidae bats species were carried out. Analysis was restricted to the external morphology, covering general shape of the tongue and its papillae. Types of papillae and their distribution presented considerable intergeneric variation, considering the strictly insectivorous feeding habits of these bats. Distribution of the data of tongue morphology is analyzed and compared with the phylogenetic schemes proposed previously and comments about evolutionary relationships among taxa were done.
Keywords: Molossidae; morphology; evolutionary relationships